Perceptual Enhancement for Arabic Reading: An Intervention to Support Fluency and Automaticity in Grade One - Elisabeth Wilson; Soohyun Jeon; Holly Cook; Helen Abadzi (Gulf Education and Social Policy Review)
Abstract This study, conducted in the United Arab Emirates, piloted a curriculum to increase early grade reading fluency. A curriculum with enhanced perceptual features, such as font size and spacing was used with grade one students in four schools to detect any significant difference in students’ reading speed and reading accuracy after one year. Three hundred forty-five grade one students participated in the pilot—174 in the intervention group and 171 in the control group (ds= 0.33 0.47). At the end of the year, students in the intervention group read more letters and words correctly on average in one minute (p <.01) and in an entire text (p <.01 for letters; p <.001 for words) than those in the control group. These results suggest that curriculum with perceptual enhancement may be useful in facilitating early Arabic reading fluency.